1961
DOI: 10.1139/o61-202
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Lead and Tin Organometallic Compounds on the Metabolism of Rat Brain Cortex Slices

Abstract: The effects of tetraethyl lead, tetraethyl tin, triethyl lead, and triethyl tin on the metabolism of rat brain cortex slices have been studied. Tetraethyl lead and tetraethyl tin inhibit the active transport of amino acids into rat brain cortex slices at concentrations and under conditions that show no effect on the glucose metabolism of the slices. Tetraethyl lead and tetraethyl tin inhibit the oxidation of L-glutamate by rat brain slices. This effect can be accounted for on the basis of the inhibitory action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1963
1963
1984
1984

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…It is generally accepted that the cell membrane, or more specifically its phospholipid layer, is the surface structure that is principally responsible not only for preventing effiux of various small molecules concentrated within cells (12) but also for transport of various amino acids (10,20). Our previous papers reported that both ctotrimazole and miconazole have a preferential affinity at Universitaetsbibliothek Giessen on May 15, 2015 http://sabouraudia.oxfordjournals.org/ from for certain membrane phospholipids of sensitive fungi (9,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that the cell membrane, or more specifically its phospholipid layer, is the surface structure that is principally responsible not only for preventing effiux of various small molecules concentrated within cells (12) but also for transport of various amino acids (10,20). Our previous papers reported that both ctotrimazole and miconazole have a preferential affinity at Universitaetsbibliothek Giessen on May 15, 2015 http://sabouraudia.oxfordjournals.org/ from for certain membrane phospholipids of sensitive fungi (9,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…However, the extent of amino acid transport into brain cortex slices is proportional to the level of ATP in the slices, and aIanine and phenylalanine have little effect on glycine transport in nerve cells (5). The mechanism of amino acid uptake by brain mitochondria is therefore deemed to be a different process from the transport of amino acids a t the brain cell membrane (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), and also a different process from the accumulation of noradrenaline by brain mitochondrial particles (221, which is inhibited by mo~aovalent cations such as sodium.…”
Section: Discussionmentioning
confidence: 99%
“…This solution was given to 5-week-old male rats intraperitoneally at a dosage of 15 mg/kg body weight once daily. At this concentration, the animals developed convulsions after five or six doses (Vardanis and Quastel, 1961). For control, the same concentration of n-propanol alone was given.…”
Section: Methodsmentioning
confidence: 99%
“…Patel et al (1974) suggested that the decreased labelling of amino acids from glucose in inorganic lead toxicity could be due to depression of glucose utilisation. Glucose uptake by brain was not inhibited, and therefore the decreased glucose utilisation was not due to decreased availability of glucose (Cremer, 1959;Vardanis and Quastel, 1961;Patel et al, 1974). The inhibition of lipoyl dehydrogenase, a component of the pyruvate dehydrogenase (PDH) and aketoglutarate dehydrogenase complexes, by lead has been reported (Ulmer and Vallee, 1969).…”
mentioning
confidence: 99%